A study of preheating characteristics according to various preheating methods for laser-assisted machining. Issue 9 (October 2016) - Hwang, Seong-Ju; Oh, Won-Jung; Lee, Choon-Man
Abstract Laser-assisted machining (LAM) is being actively studied as a new method for machining difficult-to-cut materials. In LAM, machining is performed after preheating the material using a laser. Among difficult-to-cut materials, silicon nitride, a type of ceramic material, is difficult to machine due to its high strength at high temperature and high thermal conductivity. Although machining of silicon nitride using laser-assisted turning has been performed, there are few studies and results using laser-assisted milling because it is difficult to maintain the proper preheating temperature of silicon nitride. So, in this study, three preheating methods, one-way, zig-zag, and back-and-forth, are proposed for machining silicon nitride using laser-assisted milling. The preheating effect according to the three preheating methods is analyzed by finite element analyses and experiments. And, the back-and-forth method is verified to be the most effective method.